PENTINGNYA MODEL PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS E-LEARNING DI ERA GLOBALISASI - Leni Anggraeni (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: Globalization as a result from modemity dynamic ever involve social relation which is do not so close betweentime and distance, representing the reflection ofknowledge. We could see The reality from the indication through the growth of very fast information technolory, specially internet. lrogress of the technology must be focus to the world of education not only from civic education onty, Urrt also how, to develop a methods which can keep abreast of information technology, especiallye-learning for civic education. Education Development of civic education base on e-learning nmciion is to make civic education in global era as a moderator. Education development of civic education base on e-learning can be made by appliance assist study model by exploiting internet as study source and for media too, so that study more interesting, and also items information for Education ofCivic even easily to access.